Deal breaker - Coben, Harlan, 1962- (Coben, Harlan, 1962- Myron Bolitar novel, 2024)
Deal Breaker is the debut of Myron Bolitar, a hotheaded, tenderhearted sports agent. When Myron's prize quarterback receives a call from a former girlfriend, who was believed to be dead, Myron's deal begins to so sour. Myron learns about the dark side of the business, where image and talent make you rich, but the truth can get you killed.